Community Structure of Marine Gastropod at Taruy Coastal Waters, Tutuk Tolu, East Seram, Maluku - Haumahu, Sara; Uneputty, Prulley A; Supusepa, Junita (Open Global Scientific Journal, 2024)
Background: Intertidal zone is located between high and low tide in the marine coastal waters. This zone has high diversity of marine resources, inclucing marine gastropods.Aims: The objective of this research was to analyze gastropod community structure namely ecological density, abundance, and ecological indices such as diversity index, evenness index, and dominance index at the coastal waters of Taruy Village, East Seram in May 2023. Methods: The ecological data of marine gastropods using line transect method in which was perpendicular to the coastline. Twelve transects were placed with the distance between transect is 50-m, and 5 meters between quadrates. Each gastropod in the quadrate was counted and preserved by 70% alcohol. Identification was done in Marine Science Laboratory, Faculty of Fisheries and Marine Science, Pattimura University, Ambon.Results: A total of 41 marine gastropods species found in this area, which is grouped into 5 order, 16 families, and 29 genera. Clypeomerus battilariaeformis has the highes ecological densisty and abundance. There were 19 species of marine gastropods which have lowest density and abundance. Species diversity of marine gastropods in this area is moderately categorized (H` = 2.97), while evenness index is highest (J`= 0.80), and there is no dominance species in the community (D = 0.08). Nineteen species of marine gastropods are rare species, and 13 species are common species.